The optimisation of processing conditions and the effect of nanoclay towards snap fit samples. - Othman, M.H.; Ibrahim, M.H.I.; Amin, A.M.; Y,Hashim, M.; Ng, C.H.; Osman, S.A.; Marwah, O.M.F.; Shaari, M.F.; Rafai, N.H.; Johar, M.A. (Academic Publications Ltd, 2018)
This research is about the optimisation the injection moulding processing condition to control shrinkage and warpage for the snap fit product throughout the Taguchi method in practical injection moulding. At this try out, the selected processing conditions were barrel temperature, holding pressure, injection velocity and injection holding. The materials that were mixtures of polypropylene and nanoclay with the addition of polypropylene grafted maleic-anhydride as the compatibilizer. Two formulations were chosen, with the difference of 0 wt. % and 5 wt. % of nanoclay loading. Each formulation was added with 15 wt. % of compatibilizer. The design of experiments for this project had adopted from a L943 orthogonal array of Taguchi method. By using the signal to noise ratio responses, the optimum processing condition for each formulation has been obtained, whereby the optimum barrel temperature was 240 0C, 20% for holding pressure, 10% of injection velocity and 9 seconds for injection holding time. The results showed that warpage reduced from 0.2944 mm (0 wt. % nanoclay) to 0.2061 mm (5 wt. % nanoclay). The shrinkage also reduced from 0.0453% (0 wt. % nanoclay) to 0.0320 % (5 wt. % nanoclay).The findings of this experiment shall be useful for future manufacturing process which was related to this sample and material. The originality of this research is about the optimised processing condition, the usage of new material which was polypropylene-nanoclay and the snap fit samples as the specific product